Pengaruh Disiplin, Pelatihan dan Komitmen Organisasi Terhadap Efektivitas Kerja - Edy, Edy Joko Prayitno; Parashakti, Ryani Dhyan (Lentera Ilmu Nusantara, 2023)
This study aims to analyze the effect of discipline, training and organizational commitment on work effectiveness at PT Hiba Utama. The research method used is to use quantitative research with the type of associative research with the Proposive Sampling technique. Simple regression analysis aims to examine the effect of variable X on variable Y. Discipline has a positive and significant effect on performance. These results indicate that Discipline greatly determines the performance of employees of PT Hiba Utama. This is indicated by the results of the t statistical test which shows a significance value of 0.015. The significance value of t is less than 0.05 (0.015 <0.05). The results of the t statistical test showed a significance value of 0.741. The significance value of t is greater than 0.05 (0.741 > 0.05). Thus, it can be concluded that the training variable is not significant to work effectiveness. Organizational Commitment variable has a significant effect on Work Effectiveness which shows a significance value of 0.036. The significance value of t is less than 0.05 (0.036 <0.05)